AMINO ACID AND VITAMIN COMPOSITION OF CRATAEGUS ORIENTALIS PALL - Y. S. Ikhsanov; K. M. Kusainova; G. Y. Tasmagambetova; N. T. Andasova; Y. A. Litvinenko (Academic Scientific Journal of Chemistry, 2021)
The genus hawthorn (Crataegus) belongs to the apple subfamily (Maloideae Focke) of the Rosaceae Juss family. The hawthorn genus includes about 1500 species distributed in warm temperate and subtropical regions of the northern hemisphere, mainly in North America. Over 80 wild and 90 introduced species grow on the territory of the CIS. Kazakhstan belongs to the forest-deficient regions; the forest cover of the territory is 3.87%. The hawthorn, which grows in flat areas, at the foot of the mountains, in the mountains, in the steppe and forest-steppe, is quite common here, is part of the undergrowth of deciduous forests, forms thickets with other shrubs. 7 wild-growing species are found in Kazakhstan: Crataegus almatensis A. Pojark., Crataegus pontica A. Koch, Crataegus turkestanica A. Pojark., Crataegus sanguinea Pall., Crataegus altaica Lge., Crataegus transkaspica A. Kocharus., Crataegus transkaspica A. Kocharus., The range of arboretums in Kazakhstan includes up to 40 - 50 species of hawthorn. In various elements of landscaping, hawthorns of various origins found; in particular, at least 20 species grow in urban plantings of Almaty. The hawthorn is widespread in the Northern Tien Shan Mountains: Zailiyskiy, Dzhungarskiy and Kungey Alatau. Plants of the genus Crataegus are rich in vitamins A, C, E, K and group B, and also contain sugars, flavonoids, saponins, phytosterols, glycosides, tannins, organic acids, amygdalin, essential oils. Thus, hawthorn is a promising raw material for the creation of domestic medicines. This article examines the study of the quantitative composition of amino acids and vitamins in the fruits of the species of the genus Crataegus widespread in Kazakhstan in a supercritical extract isolated and the fruits of the Crataegus orientalis Pall plant, in order to establish the possibility of using and with subsequent cultivation of the selected species